2020
DOI: 10.1038/s41419-020-03018-3
|View full text |Cite
|
Sign up to set email alerts
|

TRIM29 inhibits miR-873-5P biogenesis via CYTOR to upregulate fibronectin 1 and promotes invasion of papillary thyroid cancer cells

Abstract: Papillary thyroid cancer (PTC) is the most common endocrine tumor with an increasing incidence, has a strong propensity for neck lymph node metastasis. Limited treatment options are available for patients with advanced or recurrent metastatic disease, resulting in a poor prognosis. Tripartite motif protein 29 (TRIM29) is dysregulated in various cancer and functions as oncogene or tumor suppressor in discrete cancers. In this study, we found that both TRIM29 and fibronectin 1 (FN1) were upregulated with positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…However, the FN1 gene was found to be a key regulator in PTC development. Tripartite motif protein 29(TRIM29) promote the invasion and metastasis of PTC cells by up-regulating the expression of FN1 [23]. Furthermore, studies indicate that TGM2 activated FN1 through NF-κb to promote the invasion as well as metastasis of PTC [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the FN1 gene was found to be a key regulator in PTC development. Tripartite motif protein 29(TRIM29) promote the invasion and metastasis of PTC cells by up-regulating the expression of FN1 [23]. Furthermore, studies indicate that TGM2 activated FN1 through NF-κb to promote the invasion as well as metastasis of PTC [24].…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of lncRNAs to miRNAs biogenesis are gradually being revealed. Wu et al (2020) reported that lncRNA CYTOR represses miR-873-5p biogenesis via repressing the recruitment of DICER and TRBP to pre-miR-873 and further the cleavage of pre-miR-873. Zhang et al (2021) reported that lncRNA HOTAIRM1 represses miR-144 biogenesis via reducing pre-miR-144 stability and blocking the processing of pri-miR-144 by DROSHA.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer (PTC) is the most common endocrine cancer. TRIM29 reduces miR-873-5p expression by upregulating LINC00152 to upregulate FN1, thereby promoting PTC migration and invasion ( 32 ). LINC00152 acts as a ceRNA miR-497 sponge, downregulating its downstream target brain-derived neurotrophic factor (BDNF) to promote cell proliferation, colony formation, migration, and invasion ( 31 ).…”
Section: Function and Mechanisms Of Linc00152 In Human Cancermentioning
confidence: 99%